THE ROLE OF SOCIAL COUNCELING COUNSELING IN EDUCATION DURING THE COVID-19 PANDEMIC IN INDONESIA - Lue (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The development of science changes human life to impart intelligent technology that can have the impact of providing skills, welfare, survival, emotional balance, and being able to interact well socially, while since December 2019, the coronavirus outbreak has hit the world called the Covid-19 Pandemic, forcing human civilization must keep a distance from interacting directly with each other. One of the impacts of the Covid-19 pandemic is in the field of education, where aspects of social Guidance are needed, which are expected to be able to provide understanding and solutions to problems as a human being to understand life's problems during the pandemic. This paper is a literature study; the target is on the education of adolescent students in Indonesia because, during adolescence/puberty, the transition from childhood to adulthood who experiences confusion in life is caused by unclear tasks and roles. Society can be carried out professionally with the concept of a multicultural approach to form awareness of socialcultural pluralism, through information services and orientation services. A counselor is needed to provide professional social counseling guidance services, its implementation both in school education and in the community, in order to have the ability to understand, plan for the future, design life rationally, get a role that is in accordance with the interests and situations, conditions, abilities, and socio-economic life, which is fair with a positive value view of attitudes and behavior theoretically and practically during the Covid19 pandemic.